Perceived Effectiveness of Elder Abuse Interventions in Psychological Distress and the Design of Culturally Adapted Interventions: A Qualitative Study in the Chinese Community in Chicago - XinQi Dong; E-Shien Chang; Esther Wong; Melissa Simon (Journal of Aging Research)
This qualitative study examines US Chinese older adults’ views on the perceived effectiveness, challenges, and cultural adaptations of elder abuse interventions to psychological distress in the Chinese community in Chicago. A community-based participatory research approach was implemented to partner with the Chinese community. A total of 37 community-dwelling Chinese older adults (age 60+) participated in focus group discussions. Data analysis was based on grounded theory framework. Our findings suggest that older adults perceived social support, empowerment, and community-based interventions design as most effective to promote psychological well-being of victims. The perceived preferences were similar between elder abuse victims and non-victims. Strategies to culturally adapt evidence-based interventions were proposed with respect to nurturing filial piety values, familial integrations, and increased independence. Research and educational outreach initiatives were also discussed. This study has wide policy and practice implications for designing and deploying interventions to reduce psychological distress with respect to elder abuse outcome. Cultural relevancy of health interventions is important in the context of the Chinese communities. Collective federal, state, and community efforts are needed to support the culturally appropriate design and implementation of interventions suitable for the needs of the Chinese older adults.